Intra- and inter-protein couplings of backbone motions underlie protein thiol-disulfide exchange cascade - Wenbo Zhang (Nature Portfolio, 2018)
Abstract The thioredoxin (Trx)-coupled arsenate reductase (ArsC) is a family of enzymes that catalyzes the reduction of arsenate to arsenite in the arsenic detoxification pathway. The catalytic cycle involves a series of relayed intramolecular and intermolecular thiol-disulfide exchange reactions. Structures at different reaction stages have been determined, suggesting significant conformational fluctuations along the reaction pathway. Herein, we use two state-of-the-art NMR methods, the chemical exchange saturation transfer (CEST) and the CPMG-based relaxation dispersion (CPMG RD) experiments, to probe the conformational dynamics of B. subtilis ArsC in all reaction stages, namely the enzymatic active reduced state, the intra-molecular C10–C82 disulfide-bonded intermediate state, the inactive oxidized state, and the inter-molecular disulfide-bonded protein complex with Trx. Our results reveal highly rugged energy landscapes in the active reduced state, and suggest global collective motions in both the C10–C82 disulfide-bonded intermediate and the mixed-disulfide Trx-ArsC complex.